2023
DOI: 10.3389/fmicb.2023.1140498
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the gut microbiome by Lactobacillus johnsonii alleviates the development of acute myocardial infarction

Abstract: IntroductionThe gut microbial community, which can be disturbed or repaired by changes in the internal environment, contributes to the development of acute myocardial infarction (AMI). Gut probiotics play a role in microbiome remodeling and nutritional intervention post-AMI. A newly isolated Lactobacillus johnsonii strain EU03 has shown potential as a probiotic. Here, we investigated the cardioprotective function and mechanism of L. johnsonii through gut microbiome remodeling in AMI rats.MethodsA rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…It gets its energy from digesting hexosaccharides and disaccharides into lactic acid. Galactose, maltose, gentiose, isopropyl, isomaltose, and panthenose are specifically the sugars it employs as substrates . The genes that encode the biosynthetic pathways and essential cofactors for the production of amino acids are also absent in L. johnsonii .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It gets its energy from digesting hexosaccharides and disaccharides into lactic acid. Galactose, maltose, gentiose, isopropyl, isomaltose, and panthenose are specifically the sugars it employs as substrates . The genes that encode the biosynthetic pathways and essential cofactors for the production of amino acids are also absent in L. johnsonii .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, genome sequencing showed that L. johnsonii had all the pyrimidine-making genes required but lacked the purine-making genes. To get purine nucleotides, L. johnsonii must rely on its human host or another intestinal microbial community . Therefore, it can be hypothesized that the decrease in L. johnsonii in the earthworm gut bacteria might be caused by the fact that PE-MPs prevented earthworm gut microorganisms from absorbing environmental nutrients, thereby decreasing their energy supply.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncultured_Bacteroidales_bacterium and uncultured_rumen_bacterium of the rEg.P29 T + B + CpG group were elevated compared to those of the control group, while the unclassified_Clostridia_UCG_014 was significantly reduced. Zhong et al 61 found that enrichment of Lactobacillus johnsonii caused remodeling of the gut microbiota by increasing the abundance of Muribaculaceae and Lactobacillus and decreasing that of Clostridia UCG_014. The specific mechanisms that lead to changes in intestinal flora after vaccine immunization were explored by means of functional prediction of these differential flora.…”
Section: Discussionmentioning
confidence: 99%